Stronger perceptual filling-in of spatiotemporal information in the blind spot compared with artificial gaps - Revina, Yulia (2020)
Complete visual information about a scene and the objects within it is often not available to us. For example, objects may be partly occluded by other objects or have sections missing. In the retinal blind spot, there are no photoreceptors and visual input is not detected. However, owing to perceptual filling-in by the visual system we often do not perceive these gaps. There is a lack of consensus on how much of the mechanism for perceptual filling-in is similar in the case of a natural scotoma, such as the blind spot, and artificial scotomata, such as sections of the stimulus being physically removed. Part of the difficulty in assessing this relationship arises from a lack of direct comparisons between the two cases, with artificial scotomata being tested in different locations in the visual field compared with the blind spot. The peripheral location of the blind spot may explain its enhanced filling-in compared with artificial scotomata, as reported in previous studies. In the present study, we directly compared perceptual filling-in of spatiotemporal information in the blind spot and artificial gaps of the same size and eccentricity. We found stronger perceptual filling-in in the blind spot, suggesting improved filling-in for the blind spot reported in previous studies cannot be simply attributed to its peripheral location.